Multidimensional Poverty Among Rice Farming Workers’ Households in Bengkulu City - Lastri, Susi; Mulyasari, Gita; Trisusilo, Agung (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2025)
Poverty among rice farming workers is a multidimensional issue that extends beyond income levels, encompassing education, health, and living standards. Traditional poverty assessments based solely on income fail to capture these broader deprivations. To provide a more comprehensive analysis, this study employs the Multidimensional Poverty Index (MPI), which considers multiple well-being indicators. The study aims to analyze the multidimensional poverty status of rice farming worker households in Bengkulu City and identify the key factors influencing their poverty status. A sample of 100 rice farming workers was selected using the Mo formula to ensure representativeness. The findings reveal that 19% of rice farming worker households fall within the multidimensional poverty category, while 81% are non-poor. Among the examined factors, work experience significantly influences poverty levels, with more excellent experience contributing to a lower likelihood of poverty. The use of MPI provides a more holistic understanding of poverty, highlighting the need for policies that address not only income disparities but also access to education, healthcare, and improved living conditions. Enhancing skill development and creating stable employment opportunities are crucial for alleviating multidimensional poverty among rice farming workers in Bengkulu City.